Burnout among Registered Nurses Working at A Tertiary Care Hospital of Southern Region: Fa-is Walohtae - Walohtae, Fa-is; Nimu, Nisuraida; Doloh, Surawut; Maropi, Anuchit (Princess of Naradhiwas University Journal, 2024)
The purposes of this descriptive study were to: 1) determine the level of burnout experienced by registered nurses working at a tertiary care hospital in the southern region; and 2) investigate methods for reducing burnout among these nurses. The samples group was split into two groups: thirty samples who completed questionnaires and ten samples who chose to participate in a brief focus group discussion by choosing from the same group of samples. Two types of questionnaires were used: 1) a measurement of burnout among registered nurses which had an Alpha Cronbach’s coefficient of 0.85 and a content validity index of 1; and 2) a semi-structured interview questionnaire for focus group discussions with registered nurses which had an Alpha Cronbach’s coefficient of 0.97 and a content validity index of 1. Data analysis used descriptive statistics such as percentage, mean, standard deviation, and content analysis. Results found that an average overall burnout score for registered nurses working in a tertiary hospital in the southern region was found to be moderate (M = 2.50, SD. =0.65). When each component was examined, it was found that the working part had the highest average burnout score (M = 3.19, S.D. = 0.94), followed by the organizational part and the personal part (physical fatigue) (M = 2.68, S.D. = 0.90, M = 2.66, S.D. = 0.74) respectively, and the aspect of burnout that registered nurses experienced at the lowest level was personal part (emotional exhaustion and Cognitive weariness) (M = 1.99, S.D. = 0.69, M = 1.99, S.D. = 0.78) respectively, The following were strategies to help registered nurses who were working professionally experience less burnout: 1) sleep and rest; 2) self-care; 3) balanced nutrition; 4) working plan; 5) balanced working schedule; 6) effective communication with coworkers; 7) stress management; and 8) mental health promotion.